The Role of Artificial Intelligence in Shaping Future Media Landscapes - Dabas, Pooja (Integrated Journal for Research in Arts and Humanities, 2023)
"The Role of Artificial Intelligence in Shaping Future Media Landscapes" examines the various uses, advantages, and moral dilemmas of AI in the media. In order to comprehend how AI improves media practices while raising issues with privacy, prejudice, and disinformation, it employs a mixed-methods approach that includes case studies, literature reviews, and expert interviews. According to the report, artificial intelligence (AI) increases productivity, allows for customized user experiences, and encourages the production of interactive content, but it also brings up moral concerns such as algorithmic bias hazards, echo chambers, erosion of user privacy, and the dependence on automated systems in advertising and journalism. According to the article, in order to reduce hazards and guarantee responsible usage, strict regulation and moral supervision are necessary.